2020
DOI: 10.3390/pr8050537
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Criteria for Intelligent Systems in Motor Production Line Process Management

Abstract: In this study, the factors that affect the implementation of intelligent systems in motor production lines are analyzed. A motor production line located in Vietnam is used as the research object. The research methods include secondary data collection, field study, and interviews. This study demonstrates the following: firstly, the implementation of intelligent systems in motor production lines is heading toward Industry 4.0. Secondly, it is proposed that three functional systems—robot arm, image recognition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The objective is to strive to put into practice this concept, which will allow flexible decision-making and smart manufacturing systems, as anticipated by the Industry 4.0 concept. Therefore, by turning Industry 4.0 a reality, the role of the Internet of Things (IoT) and additional emergent technologies will have a central role [7]. So far, the tendency to have unmanned operations and increasing automation in semiconductor production systems, as in other production technologies, is constantly growing [8].…”
Section: Of 38mentioning
confidence: 99%
“…The objective is to strive to put into practice this concept, which will allow flexible decision-making and smart manufacturing systems, as anticipated by the Industry 4.0 concept. Therefore, by turning Industry 4.0 a reality, the role of the Internet of Things (IoT) and additional emergent technologies will have a central role [7]. So far, the tendency to have unmanned operations and increasing automation in semiconductor production systems, as in other production technologies, is constantly growing [8].…”
Section: Of 38mentioning
confidence: 99%
“…Results show that the degree of superheat and the injection duration both decreased with the release pressure. Lin et al [20] analyze the factors that affect the implementation of intelligent systems in motor production lines. Their research results can be provided as a reference for production lines that acquaint with intelligent systems.…”
Section: Other Issuesmentioning
confidence: 99%
“…According to the theoretical basis in [28], the research into big data solutions focuses on monitoring, forecasting, data analysis, and proposing solutions, which is consistent with the basic hypothesis of this study. The latest research [30] shows that the object of this study has gradually moved towards intelligent system processes. The results of this study determine that the intelligent process is correct and predictable.…”
Section: Conclusion and Further Recommendationsmentioning
confidence: 99%
“…In terms of research implications, linear regression and machine learning, most results of the tests supported the research hypothesis. This research is focused on customer driven sustainable development, because big data requires that customers request their data to be collected, and every shipment must include data for all products, because a customer needs to confirm and track the quality of such products, to ensure the reliability of the end products that they manufacture [30]. This study found a link between Industry 4.0 and sustainability.…”
Section: Conclusion and Further Recommendationsmentioning
confidence: 99%